PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN GEOGEBRA - Nadiya Ahsani Salsabilla; Bana G. Kartasasmita; Jusep Saputra (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2023)
The aims of this study were to: 1) Know the improvement in the mathematical communication abilities of students who received the Geogebra-assisted Problem Based Learning model was better than students who received conventional learning models. 2) Knowing the Self-confidence of students who get the Geogebra-assisted Problem Based Learning model is better than students who get conventional learning models. 3) Knowing that there is a correlation between mathematical communication ability and self-confidence of students who obtain the Geogebra-assisted Problem Based Learning model. The method used is quasi-experimental. The subjects in this study were students of SMPN 16 Bandung. Data analysis technique with a two-sample comparison test (t-test) using the IBM SPSS 23.0 for Windows software program. Based on the results of data analysis, the following conclusions are obtained: 1) Improved mathematical communication ability of students who get the Geogebra-assisted Problem Based Learning model are better than students who get conventional learning models. 2) Self-confidence of students who use the Geogebra-assisted Problem Based Learning model is better than students who receive conventional learning models. 3) There is a correlation between mathematical communication ability and self-confidence of students who obtain the Geogebra-assisted Problem Based Learning model.